The development and pre-testing of attitude and practice questionnaire on ethical decision-making during a pandemic among medical doctors working in paediatric setting in Malaysia - Idriss, Kader Nawaaz
Background: Malaysia is facing a widespread COVID-19 pandemic which has affected clinical admission to hospitals. As the epidemiological curve is on the rise globally, the decision making for admission, ventilation, and aggressive management for COVID-19 patients, especially children, can be challenging. However, currently no single tool exists to simultaneously evaluate the domains for attitude and practice on ethical-decisions making for children during the pandemic. The current study aims to develop and validate an attitude and practice questionnaire on ethical decision-making during a pandemic among medical doctors working in paediatric setting. Methods: Relevant domains were identified to generate items and form a research tool through literature reviews, research construct and opinions of experts. The questionnaire then underwent a series of validation process that included content and face validity. Results: The developed questionnaire demonstrated a satisfactory item-level content validity index and face validity. The minimum I-CVI of the attitude items was 0.80, and the maximum was 1.00, while the minimum and maximum I-CVI for practice items were 0.80 and 1.00. Item-level face validity index (I-FVI) of 1.00 for both domains were obtained showed all the items were above the cut-off value of 0.78. All the items had satisfactory factor loading Cronbach’s alpha (>0.6). Conclusion: This study showed good level of content validity and reliability in the new questionnaire. The instrument is valid, and thus reliable to be used for assessing attitude and practice on ethical decision-making during a pandemic among Medical Doctors working in paediatric setting.